Nausea and vomiting in gastroparesis: similarities and differences in idiopathic and diabetic gastroparesis. Issue 12 (27th June 2016) - Parkman, H. P.; Hallinan, E. K.; Hasler, W. L.; Farrugia, G.; Koch, K. L.; Calles, J.; Snape, W. J.; Abell, T. L.; Sarosiek, I.; McCallum, R. W.; Nguyen, L.; Pasricha, P. J.; et al.
Abstract: Background: Nausea and vomiting are classic symptoms of gastroparesis. It remains unclear if characteristics of nausea and vomiting are similar in different etiologies of gastroparesis. The aims of this article were as follows: to describe characteristics of nausea and vomiting in patients with gastroparesis and to determine if there are differences in nausea and vomiting in diabetic (DG) and idiopathic gastroparesis (IG). Methods: Gastroparetic patients enrolling in the NIDDK Gastroparesis Registry underwent assessment with history and questionnaires assessing symptoms, quality of life, and a questionnaire characterizing nausea and vomiting. Key Results: Of 159 gastroparesis patients (107 IG, 52 DG), 96% experienced nausea, whereas 65% experienced vomiting. Nausea was predominant symptom in 28% and vomiting was predominant in 4%. Nausea was severe or very severe in 41%. PAGI‐SYM nausea/vomiting subscore was greater with increased vomiting severity, but not nausea severity in DG than IG. Nausea was related to meals in 71%; lasting most of the day in 41%. Increasing nausea severity was related to decreased quality of life. Nausea often preceded vomiting in 82% of patients and vomiting often relieved nausea in 30%. Vomiting was more common in DG (81%) compared to IG (57%; p = 0.004). Diabetic patients more often had vomiting in the morning before eating, during the night, and when not eating. Conclusions & Inferences: Nausea is present in essentially all patients with gastroparesis irrespective of cause and associated with decreased quality of life. In contrast, vomiting was more prevalent, more severe, and occurred more often in DG than IG. Thus, characteristics of vomiting differ in IG vs DG.